Characterization and evaluation of three new strains of Beauveria bassiana isolated from Musca domestica L. (Diptera: Muscidae) - de Abajo, Juan Manuel (2024)
Musca domestica L. is a cosmopolitan pest usually reaching high population levels, causing substantial economic losses and also acting as a vector for many diseases. The use of entomopathogenic fungi as a replacement of the chemical insecticides is a possibility already studied. In this study, we isolated three strains of Beauveria bassiana from naturally infected M. domestica individuals and tested their potentiality to act as a biological control agent. The finding of naturally occurring entomopathogenic fungal infections indicates that these fungi are well-adapted to the local environment and can survive and thrive under natural conditions, making them promising candidates for biological pest management.